Pengaruh Metode Field Trip Berbasis Budaya Batik Khas Solo terhadap Kemampuan Menulis Teks Berita Siswa Kelas VIII SMP Al Muayyad Surakarta - Nindy Advianturi; Ahmad Alfi; Kaito Murayama (UIN Raden Mas Said Surakarta, Indonesia, 2024)
The ability to write news articles is an essential skill that students must possess. Learning by inviting students to observe objects directly makes students more able to develop their ideas and creativity. Solo is a city that is synonymous with batik culture. This research was conducted to investigate the impact of applying a field trip method focused on the cultural batik of Solo on the news writing skills of eighth-grade students at Al Muayyad Junior High School in Surakarta. This study employs a quasi-experimental approach with a non-equivalent control group design, involving pretests and posttests. There are two classes: the experimental class and the control class. The experimental class was conducted using the field trip method by inviting students to explore the Laweyan batik village, while the control class was conducted with non-field trip learning. Data collection was carried out through tests that assess learning outcomes or projects after giving the action. The results showed that there was a significant effect of the field trip method based on the typical Solo batik culture on the ability to write news texts for the VIII grade students of SMP Al Muayyad Surakarta. Cohen's d analysis shows that the effect is quite large. Students in the field trip class have significantly higher news writing skills than those in the non-field trip class. Keterampilan menulis berita adalah salah satu kemampuan penting yang harus dikuasai oleh siswa. Pembelajaran dengan mengajak siswa mengamati objek secara langsung membuat siswa menjadi lebih bisa memgembangkan ide dan kreatifitasnya. Solo merupakan kota yang identik dengan budaya batik. Penelitian ini dilaksanakan untuk menginvestigasi dampak penerapan metode field trip yang berfokus pada budaya batik khas Solo terhadap kemampuan menulis berita siswa kelas VIII di SMP Al Muayyad Surakarta. Penelitian ini menggunakan pendekatan eksperimental kuasi dengan desain kelompok kontrol non-setara, melibatkan pengujian awal dan pengujian akhir. Terdapat dua kelas, eksperimen dan kontrol. Kelas eksperimen dilaksanakan dengan menerapkan metode field trip dengan mengajak siswa menjelajah kampung batik Laweyan, sedangkan kelas kontrol dilakukan dengan pembelajaran non field trip. Pengumpulan data dilakukan melalui tes yang mengukur hasil belajar atau proyek setelah pemberian tindakan. Hasil penelitian menunjukan adanya pengaruh yang signifikan metode field trip berbasis budaya batik khas Solo terhadap kemampuan menulis teks berita siswa kelas VIII SMP Al Muayyad Surakarta. Analisis d Cohen menunjukan efeknya tergolong besar. Siswa di kelas field trip memiliki kemampuan menulis berita yang jauh lebih tinggi daripada di kelas non field trip.